Vitamin D and risk of pregnancy related hypertensive disorders: mendelian randomisation study. (20th June 2018) - Magnus, Maria C; Miliku, Kozeta; Bauer, Anna; Engel, Stephanie M; Felix, Janine F; Jaddoe, Vincent W V; Lawlor, Debbie A; London, Stephanie J; Magnus, Per; McGinnis, Ralph; Nystad, Wenche; Page, Christian M; et al.
Abstract: Objective: To use mendelian randomisation to investigate whether 25-hydroxyvitamin D concentration has a causal effect on gestational hypertension or pre-eclampsia. Design: One and two sample mendelian randomisation analyses. Setting: Two European pregnancy cohorts (Avon Longitudinal Study of Parents and Children, and Generation R Study), and two case-control studies (subgroup nested within the Norwegian Mother and Child Cohort Study, and the UK Genetics of Pre-eclampsia Study). Participants: 7389 women in a one sample mendelian randomisation analysis (751 with gestational hypertension and 135 with pre-eclampsia), and 3388 pre-eclampsia cases and 6059 controls in a two sample mendelian randomisation analysis. Exposures: Single nucleotide polymorphisms in genes associated with vitamin D synthesis (rs10741657 and rs12785878) and metabolism (rs6013897 and rs2282679) were used as instrumental variables. Main outcome measures: Gestational hypertension and pre-eclampsia defined according to the International Society for the Study of Hypertension in Pregnancy. Results: In the conventional multivariable analysis, the relative risk for pre-eclampsia was 1.03 (95% confidence interval 1.00 to 1.07) per 10% decrease in 25-hydroxyvitamin D level, and 2.04 (1.02 to 4.07) for 25-hydroxyvitamin D levels <25 nmol/L compared with ≥75 nmol/L. No association was found for gestational hypertension. The one sample mendelian randomisation analysis using the total genetic risk score as an instrument did not provide strong evidence of a linear effect of 25-hydroxyvitamin D on the risk of gestational hypertension or pre-eclampsia: odds ratio 0.90 (95% confidence interval 0.78 to 1.03) and 1.19 (0.92 to 1.52) per 10% decrease, respectively. The two sample mendelian randomisation estimate gave an odds ratio for pre-eclampsia of 0.98 (0.89 to 1.07) per 10% decrease in 25-hydroxyvitamin D level, an odds ratio of 0.96 (0.80 to 1.15) per unit increase in the log(odds) of 25-hydroxyvitamin D level <75 nmol/L, and an odds ratio of 0.93 (0.73 to 1.19) per unit increase in the log(odds) of 25-hydroxyvitamin D levels <50 nmol/L. Conclusions: No strong evidence was found to support a causal effect of vitamin D status on gestational hypertension or pre-eclampsia. Future mendelian randomisation studies with a larger number of women with pre-eclampsia or more genetic instruments that would increase the proportion of 25-hydroxyvitamin D levels explained by the instrument are needed.